PENGARUH BRAND EXPERIENCE DAN SYMBOLIC VALUE TERHADAP BRAND LOYALTY KONSUMEN iPHONE DENGAN ACTUAL SELF-CONGRUENCY DAN CUSTOMER INVOLVEMENT SEBAGAI VARIABEL INTERVENING - Ernita Vania; I Made Bayu Dirgantara (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of actual self-congruency and customer involvement who get the influence of brand experience and symbolic value on brand loyalty. Sampling was used using a purposive sampling technique, the total sample used was 256 respondents who are consumers of Apple iPhone products who still use Apple iPhone products, who have had an Apple iPhone more than once and who have changed products from Apple iPhone to Android. The data analysis technique used in this research is using SEM (structural equation model) analysis with the AMOS program, and data collection techniques using a questionnaire. The results show that brand experience has a positive effect on the actual self-congruency of consumers of Apple iPhone products, actual self-congruency has a positive effect on brand loyalty, symbolic value has a positive effect on actual self-congruency, symbolic value has a positive effect on customer involvement, actual self-congruency has a positive effect on customer involvement and customer involvement have a positive effect on consumer brand loyalty for Apple iPhone products.